Perovskite-based thin film laminated solar cell and preparation method thereof

By introducing nano-silica porous interface layer and ionic liquid self-healing polymers into perovskite solar cells, the stability and interface problems of perovskite solar cells are solved, the photoelectric conversion efficiency and mechanical stability are improved, and the photoelectric conversion efficiency and mechanical stability are extended. The service life of the battery realizes high-performance perovskite-based thin-film stacked solar cells.

CN119300677APending Publication Date: 2025-01-10NINGBO OSDA SOLAR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411412708.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional perovskite solar cells have stability and durability problems during long-term operation. Chemical instability and interface problems affect the charge extraction and transmission efficiency, limiting their commercial applications.

Method used

The nano-silica porous interface layer and self-healing polymer containing ionic liquid are introduced, and a modified perovskite absorption layer is formed through spin coating and heat treatment, which enhances the stability and self-healing ability of the battery and optimizes interface contact and charge transport.

Benefits of technology

It significantly improves the photoelectric conversion efficiency and mechanical stability of perovskite-based thin-film stacked solar cells, extends the service life of the battery, and meets the needs of high-performance solar cells.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a perovskite-based thin film laminated solar cell, and the method comprises the following steps: S1, taking transparent conductive glass as a substrate, and carrying out the spin coating of an electron transmission material on the substrate to form an electron transmission layer; s2, a perovskite precursor solution prepared in advance is spin-coated, and a perovskite absorption layer is obtained after primary heat treatment; s3, depositing a nano silicon dioxide porous interface layer, spin-coating a self-repairing polymer containing ionic liquid, and performing secondary heat treatment to obtain a modified perovskite absorption layer; s4, spin-coating a hole transport layer; s5, performing vacuum evaporation on a metal counter electrode layer to obtain a perovskite top cell; and S6, stacking and compounding the perovskite-based thin film and a crystal silicon bottom cell to form the perovskite-based thin film laminated solar cell. According to the preparation method of the perovskite-based thin film laminated solar cell, the photoelectric conversion efficiency and the stability of the cell are improved, the self-repairing capability and the long-term durability of the cell are enhanced, and the high-standard requirement of commercial application can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite-based thin-film stacked solar cell and a preparation method thereof. Background Art

[0002] Perovskite-based thin-film stacked solar cells have attracted much attention due to their high photoelectric conversion efficiency and low-cost preparation process. Traditional perovskite solar cells usually use a single perovskite layer as a light-absorbing material. However, such cells often encounter stability and durability issues during long-term operation. The chemical instability of perovskite materials and their sensitivity to environmental factors (such as humidity and temperature changes) limit their commercialization process. In addition, the interface problems between the perovskite layer and the electron transport layer or hole transport layer also affect the charge extraction and transfer efficiency, thereby affecting the overall performance of the battery.

[0003] In order to improve the performance and stability of perovskite solar cells, researchers have tried a variety of methods, including optimizing the composition of perovskite materials, introducing new electron and hole transport materials, and developing new interface engineering strategies. Although some progress has been made, how to further enhance the stability of the perovskite layer, improve interface problems, and improve the long-term stability of the battery remains a major challenge in this field. Therefore, exploring new preparation methods and materials to achieve more efficient and stable perovskite-based thin-film stacked solar cells has important scientific research and industrial application value. Summary of the invention

[0004] In view of the above shortcomings of the prior art, the present invention provides a method for preparing a perovskite-based thin-film stacked solar cell to solve the shortcomings of traditional solar cells in terms of stability, efficiency, and long-term durability. By introducing a nano-silicon dioxide porous interface layer and a self-healing polymer containing an ionic liquid, the present invention not only improves the photoelectric conversion efficiency of the perovskite-based thin-film stacked solar cell, but also significantly enhances its stability and self-healing ability under different environmental conditions, thereby extending the service life of the battery and meeting the market demand for high-performance solar cells.

[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0006] A method for preparing a perovskite-based thin-film stacked solar cell, the method comprising the following steps:

[0007] S1: using a transparent conductive glass as a substrate, spin coating an electron transport material on the transparent conductive glass to form an electron transport layer;

[0008] S2: Spin-coating the pre-prepared perovskite precursor solution on the electron transport layer obtained in step S1, and obtaining the perovskite absorption layer after a heat treatment;

[0009] S3: depositing a nano-silica porous interface layer on the perovskite absorption layer obtained in step S2, and then spin-coating a self-healing polymer containing an ionic liquid to form a pre-filled self-healing network, and obtaining a modified perovskite absorption layer after a secondary heat treatment;

[0010] S4: spin coating a hole transport layer on the modified perovskite absorption layer obtained in step S3;

[0011] S5: vacuum evaporating a metal counter electrode layer on the hole transport layer obtained in step S4 to obtain a perovskite top cell;

[0012] S6: The perovskite top cell obtained in step S5 is stacked and compounded with the crystalline silicon bottom cell to form the perovskite-based thin-film stacked solar cell.

[0013] As a preferred technical solution, the electron transport material includes but is not limited to at least one of titanium dioxide, tin dioxide, and zinc oxide.

[0014] As a preferred technical solution, a light-to-heat conversion material layer is introduced between the perovskite absorption layer and the nanoporous protective layer by spraying or spin coating.

[0015] As a preferred technical solution, the light-to-heat conversion material layer is carbon nanotubes or graphene.

[0016] The present application introduces a photothermal conversion material layer of carbon nanotubes or graphene, which not only helps to increase the short-circuit current of the battery, but also may increase the open-circuit voltage, thereby directly enhancing the photoelectric conversion efficiency of the battery. In addition, the photothermal conversion material layer helps to disperse and manage the heat inside the system, reduce local overheating, and thus improve the thermal stability of the battery.

[0017] As a preferred technical solution, the nano-silica porous interface layer is prepared by at least one of chemical vapor deposition, atomic layer deposition, sol-gel method and template method.

[0018] As a preferred technical solution, the self-healing polymer containing ionic liquid is obtained by compounding a polymer obtained by a partial alcoholysis product of PET and a disulfide dibasic acid modification reaction with an ionic liquid.

[0019] As a preferred technical solution, the preparation method of the PET partial alcoholysis product is as follows: polyethylene terephthalate (PET) and ethanol are mixed in a molar ratio of 1:4, reacted at 130°C for 4 hours under nitrogen protection, and the PET partial alcoholysis product is obtained, and the alcoholysis degree of the PET partial alcoholysis product is controlled at 50-70%. During the alcoholysis process, the ethylene glycol unit of PET is partially replaced by ethanol to form a PET partial alcoholysis product containing hydroxyl groups. The alcoholysis degree of the partial alcoholysis product is controlled between 50% and 70% to ensure that the product has sufficient hydroxyl groups and can maintain a certain molecular weight and mechanical strength. After the reaction is completed, the unreacted ethanol is removed by distillation to obtain a PET partial alcoholysis product, which will be used for subsequent modification reaction with disulfide dibasic acid to prepare a self-healing polymer containing ionic liquid.

[0020] As a preferred technical solution, the disulfide dibasic acid is at least one of 3,3'-dithiodipropionic acid, 8,8'-dithiodi-octanoic acid, 4,4'-dithiodibenzoic acid, 2,2'-dithiodibenzoic acid, and 3,3'-disulfide dibenzoic acid. The present application utilizes the disulfide bond (SS) in the molecular structure of disulfide dibasic acid, which has unique dynamic self-healing properties. These disulfide bonds can break when subjected to external stress or damage and reform under appropriate conditions, thereby giving the perovskite layer the ability to self-repair. This self-repairing mechanism significantly improves the resilience of the battery after minor damage and maintains the performance and integrity of the battery. In addition, by introducing a self-healing polymer containing a disulfide dibasic acid, the chemical interaction with the perovskite absorption layer is enhanced, forming a more stable chemical bond, thereby further improving the chemical stability of the battery.

[0021] As a preferred technical solution, the ionic liquid is at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4), 1-ethyl-3-methylimidazolium hexafluorophosphate (EMIM-PF6), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM-TFSI), 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM-BF4), 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF6), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIM-TFSI), 1-hexyl-3-methylimidazolium tetrafluoroborate (HMIM-BF4), 1-hexyl-3-methylimidazolium hexafluorophosphate (HMIM-PF6), and 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (HMIM-TFSI).

[0022] As a preferred technical solution, the operating conditions of the primary heat treatment are heating at 100-150°C for 10-30 minutes; the operating conditions of the secondary heat treatment are heating at 140-160°C for 1-2 hours, then heating to 200°C at a rate of 3-5 per minute in a nitrogen atmosphere, and maintaining for 0.5-1 hour, and finally naturally cooling to room temperature in a nitrogen atmosphere.

[0023] This application not only enhances the chemical and environmental stability of the battery by introducing a porous nano-silica interface layer, but the porous structure also facilitates the penetration of self-healing polymers, allowing the battery to quickly self-repair when damaged and maintain its performance and integrity. The secondary heat treatment step further enhances the bond between the self-healing polymer and the perovskite layer, ensuring the long-term durability and stability of the battery. In addition, the presence of the porous nano-silica interface layer may also improve the interface contact between the perovskite absorption layer and the hole transport layer, optimize the extraction and transfer of charges, and improve the overall performance of the battery.

[0024] Another aspect of the present invention is to provide a perovskite-based thin-film tandem solar cell, wherein the solar cell is prepared by the above-mentioned method for preparing the perovskite-based thin-film tandem solar cell.

[0025] Beneficial effects of the present invention:

[0026] The preparation method of the perovskite-based thin-film stacked solar cell of the present invention not only effectively protects the perovskite layer, but also realizes the self-repair and stability improvement of the battery performance by innovatively introducing a nano-silicon dioxide porous interface layer between the electron transport layer and the perovskite absorption layer, and combining it with a self-repairing polymer containing an ionic liquid. This design not only enhances the mechanical stability and self-repairing ability of the battery, but also maintains the high photoelectric conversion efficiency of the battery, which helps to improve the long-term stability and reliability of the battery.

[0027] In general, the perovskite-based thin-film tandem solar cell of the present invention not only has excellent photoelectric conversion efficiency and good mechanical stability, but also ensures its long-term durability and stability under various environmental conditions. The overall comprehensive performance and environmental adaptability are strong, which can meet the high standards of commercial applications and provide new possibilities for the development of solar cell technology. DETAILED DESCRIPTION

[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0029] Example 1

[0030] The method for preparing a perovskite-based thin-film stacked solar cell in this embodiment comprises the following steps:

[0031] S1: Using transparent conductive glass as a substrate, spin-coating a titanium dioxide electron transport material on the transparent conductive glass to form an electron transport layer.

[0032] S2: Spin-coat the pre-prepared perovskite precursor solution on the electron transport layer obtained in step S1, and obtain the perovskite absorption layer after a heat treatment; the preparation method of the perovskite precursor solution is: add 10g chitosan to 1L mixed solution composed of 0.5mol / L lead iodide, 0.15mol / L cesium iodide and 0.35mol / L methylamine iodide (the solvent is N,N-dimethylformamide, DMF), and dissolve to form a perovskite precursor solution. The operating condition of the single heat treatment is heating at 120°C for 30 minutes. Further, a carbon nanotube photothermal conversion material layer is introduced on the perovskite absorption layer by spin coating.

[0033] S3: depositing a nano-silica porous interface layer on the perovskite absorption layer obtained in step S2, and then spin-coating a self-healing polymer containing an ionic liquid to form a pre-filled self-healing network, and obtaining a modified perovskite absorption layer after secondary heat treatment; the operating conditions of the secondary heat treatment are 150°C for 2 hours, and then heating to 200°C at a rate of 5 per minute in a nitrogen atmosphere, and maintaining for 0.5 hours, and finally naturally cooling to room temperature in a nitrogen atmosphere.

[0034] S4: Spin-coating a F4TCNQ hole transport layer on the modified perovskite absorption layer obtained in step S3.

[0035] S5: Vacuum evaporate an aluminum metal counter electrode layer on the hole transport layer obtained in step S4 to obtain a perovskite top cell.

[0036] S6: The perovskite top cell obtained in step S5 is stacked and compounded with the TOPCon crystalline silicon bottom cell through a P-type microcrystalline silicon bonding layer to form the perovskite-based thin-film stacked solar cell.

[0037] The nano-silica porous interface layer is prepared by a sol-gel method. Specifically, the following steps are included: first, tetraethyl orthosilicate (TEOS) is slowly added dropwise to a mixed solvent consisting of ethanol and deionized water in a volume ratio of 4:3; then, ammonia water is added as a catalyst to promote the hydrolysis and polycondensation reaction of TEOS, and the addition is performed according to a molar ratio of TEOS to ammonia water of 1:2; under stirring conditions, the mixed solution is aged at room temperature for several hours to form a stable sol, and then, it is further aged in a vacuum drying oven at 60°C to promote the further development of the gel network, and then dried at room temperature after aging to remove the residual solvent; then, the dried gel is heat-treated at a high temperature of 820°C to solidify the gel and form the final porous silica interface layer, and a porous structure with a pore size distribution between 100nm and 300nm is obtained.

[0038] The self-healing polymer containing ionic liquid is obtained by compounding the polymer after the partial alcoholysis product of PET and the disulfide dibasic acid modification reaction with the ionic liquid. Specifically, the following steps are included: first, polyethylene terephthalate (PET) and ethanol are mixed in a molar ratio of 1:4, and reacted at 130°C for 4 hours under nitrogen protection to obtain a partial alcoholysis product of PET, and the alcoholysis degree of the partial alcoholysis product of PET is controlled at 50-70%; then the partial alcoholysis product of PET and 3,3'-dithiodipropionic acid are dissolved in dimethyl sulfoxide, and a catalytic amount of sulfuric acid is added, and the reaction is heated to 120°C for 2 hours to obtain a self-healing polymer, and finally, the polymer is compounded with EMIM-BF4 ionic liquid in a mass ratio of 10:1 to obtain the self-healing polymer containing ionic liquid.

[0039] Comparative Example 1

[0040] The raw material composition and preparation steps of the preparation method of the perovskite-based thin-film stacked solar cell of this comparative example are basically the same as those of Example 1, except that the preparation method of this comparative example does not include step S3.

[0041] The photoelectric conversion efficiency test of the perovskite-based thin-film stacked solar cell of Example 1 and Comparative Example 1 was carried out under a standard solar simulator, simulating the illumination condition of AM 1.5G, with an illumination intensity of 100 mW / cm 2 The test results show that the photoelectric conversion efficiency of the battery reaches 21.5%, which is 3.3 percentage points higher than 18.2% of Comparative Example 1. The short-circuit current density of the battery in Example 1 is 40.0 mA / cm 2, the open circuit voltage is 1.15V, and the fill factor is 0.82. In the stability test, after the battery has been running continuously for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 95%, while the battery performance of Comparative Example 1 drops to 82%. In addition, the moisture resistance test shows that the performance of the battery of Example 1 did not drop significantly after running for 500 hours under 95% relative humidity, while the performance of the battery of Comparative Example 1 dropped by 11%. The heat resistance test also shows that the performance of the battery of Example 1 did not drop significantly after running for 500 hours under 95°C, while the performance of the battery of Comparative Example 1 dropped by 6%. These test results show that by introducing a nano-silica porous interface layer and a self-healing polymer containing an ionic liquid, the battery of Example 1 has significantly improved in terms of photoelectric conversion efficiency, stability, and moisture and heat resistance.

[0042] Example 2

[0043] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the electron transport material uses tin dioxide instead of the titanium dioxide in Example 1; the photothermal conversion material layer uses graphene instead of the carbon nanotubes in Example 1; the disulfide dibasic acid uses 8,8'-dithiodi-octanoic acid instead of 3,3'-dithiodipropionic acid in Example 1; and the ionic liquid uses 1-ethyl-3-methylimidazolium hexafluorophosphate (EMIM-PF6) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0044] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 20.8%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 94%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0045] Example 3

[0046] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the electron transport material uses zinc oxide instead of the titanium dioxide in Example 1; the photothermal conversion material layer uses graphene instead of the carbon nanotubes in Example 1; the disulfide dibasic acid uses 4,4'-dithiodibenzoic acid instead of 3,3'-dithiodipropionic acid in Example 1; and the ionic liquid uses 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM-TFSI) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0047] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 21.2%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 96%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0048] Example 4

[0049] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the disulfide dibasic acid uses 2,2'-dithiodibenzoic acid instead of 3,3'-dithiodipropionic acid in Example 1; the ionic liquid uses 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM-BF4) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0050] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 20.9%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 95%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0051] Example 5

[0052] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the electron transport material uses tin dioxide instead of the titanium dioxide in Example 1; the disulfide dibasic acid uses 3,3'-disulfide dibenzoic acid instead of 3,3'-dithiodipropionic acid in Example 1; and the ionic liquid uses 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF6) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0053] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 21.1%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 94%; after operating for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0054] Example 6

[0055] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the electron transport material uses zinc oxide instead of the titanium dioxide in Example 1; the photothermal conversion material layer uses graphene instead of the carbon nanotubes in Example 1; the disulfide dibasic acid uses 8,8'-dithiodi-octanoic acid instead of 3,3'-dithiodipropionic acid in Example 1; and the ionic liquid uses 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BMIM-TFSI) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0056] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 20.1%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 94%; after operating for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0057] Example 7

[0058] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the photothermal conversion material layer uses graphene instead of the carbon nanotubes in Example 1; the disulfide dibasic acid uses 2,2'-dithiodibenzoic acid instead of 3,3'-dithiodipropionic acid in Example 1; and the ionic liquid uses 1-hexyl-3-methylimidazolium tetrafluoroborate (HMIM-BF4) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0059] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 21.4%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 96%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0060] Example 8

[0061] The preparation method of the perovskite-based thin-film stacked solar cell of this embodiment has the same raw material composition and preparation steps as those of Example 1, except that, in the preparation method of this embodiment, the disulfide dibasic acid uses 4,4'-dithiodibenzoic acid instead of 3,3'-dithiodipropionic acid in Example 1; and the ionic liquid uses 1-hexyl-3-methylimidazolium hexafluorophosphate (HMIM-PF6) instead of 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM-BF4) in Example 1.

[0062] The test results show that the photoelectric conversion efficiency of the battery of this embodiment reaches 21.2%; after continuous operation for 1000 hours in an environment of 85°C and 85% relative humidity, its initial efficiency remains at 95%; after running for 500 hours under 95% relative humidity and 95°C conditions, there is no obvious decline in performance.

[0063] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A method for preparing a perovskite-based thin-film stacked solar cell, characterized in that: The preparation method comprises the following steps: S1: using a transparent conductive glass as a substrate, spin coating an electron transport material on the transparent conductive glass to form an electron transport layer; S2: Spin-coating the pre-prepared perovskite precursor solution on the electron transport layer obtained in step S1, and obtaining the perovskite absorption layer after a heat treatment; S3: depositing a nano-silica porous interface layer on the perovskite absorption layer obtained in step S2, and then spin-coating a self-healing polymer containing an ionic liquid to form a pre-filled self-healing network, and obtaining a modified perovskite absorption layer after a secondary heat treatment; S4: spin coating a hole transport layer on the modified perovskite absorption layer obtained in step S3; S5: vacuum evaporating a metal counter electrode layer on the hole transport layer obtained in step S4 to obtain a perovskite top cell; S6: The perovskite top cell obtained in step S5 is stacked and compounded with the crystalline silicon bottom cell to form the perovskite-based thin-film stacked solar cell.

2. The method for preparing a perovskite-based thin film stacked solar cell according to claim 1, characterized in that: A photothermal conversion material layer is also introduced between the perovskite absorption layer and the nanoporous protective layer by spraying or spin coating.

3. The method for preparing a perovskite-based thin film stacked solar cell according to claim 2, characterized in that: The light-to-heat conversion material layer is carbon nanotubes or graphene.

4. The method for preparing a perovskite-based thin film stacked solar cell according to claim 1, characterized in that: The nano-silicon dioxide porous interface layer is prepared by at least one of chemical vapor deposition, atomic layer deposition, sol-gel method and template method.

5. The method for preparing a perovskite-based thin film stacked solar cell according to claim 1, characterized in that: The self-repairing polymer containing ionic liquid is obtained by compounding a polymer obtained by a partial alcoholysis product of PET and a disulfide dibasic acid modification reaction with an ionic liquid.

6. The method for preparing a perovskite-based thin film stacked solar cell according to claim 5, characterized in that: The preparation method of the PET partial alcoholysis product is as follows: polyethylene terephthalate and ethanol are mixed in a molar ratio of 1:4, reacted at 130° C. for 4 hours under nitrogen protection, and the PET partial alcoholysis product is obtained; the alcoholysis degree of the PET partial alcoholysis product is controlled at 50-70%.

7. The method for preparing a perovskite-based thin film stacked solar cell according to claim 5, characterized in that: The disulfide dibasic acid is at least one of 3,3'-dithiodipropionic acid, 8,8'-dithiodi-octanoic acid, 4,4'-dithiodibenzoic acid, 2,2'-dithiodibenzoic acid, and 3,3'-dithiodibenzoic acid.

8. The method for preparing a perovskite-based thin-film tandem solar cell according to claim 5, characterized in that: The ionic liquid is at least one of EMIM-BF4, EMIM-PF6, EMIM-TFSI, BMIM-BF4, BMIM-PF6, BMIM-TFSI, HMIM-BF4, HMIM-PF6, and HMIM-TFSI.

9. The method for preparing a perovskite-based thin film stacked solar cell according to claim 1, characterized in that: The operating conditions of the primary heat treatment are heating at 100-150°C for 10-30 minutes; the operating conditions of the secondary heat treatment are heating at 140-160°C for 1-2 hours, then heating to 200°C at a rate of 3-5 per minute in a nitrogen atmosphere, and maintaining for 0.5-1 hour, and finally naturally cooling to room temperature in a nitrogen atmosphere.

10. A perovskite-based thin-film tandem solar cell, characterized in that: The solar cell is prepared by the method for preparing a perovskite-based thin-film stacked solar cell according to any one of claims 1 to 9.

Citation Information

Cited By

  • Full-perovskite laminated solar cell based on intelligent self-repairing tunneling layer and preparation method of full-perovskite laminated solar cell

    CN120112057A

  • Bionic perovskite silicon nanoparticle photovoltaic cell and preparation method thereof

    CN122138568A